(untitled) (International Journal of Physiotherapy, 2020)
Background: Patients after breast cancer (BC) surgery have expressed the need for better care and instruction. This need is presently more evident than ever, with post-surgical hospitalization shortened to a minimum due to the Covid-19 pandemic. Online instruction may improve care for these women. Purpose: To develop a standard physical therapy instruction sheet for women after BC surgery, which can also be made available online. Methods: This clinical letter presents instructions based on a literature review, on recent recommendations to reduce the risk of side effects after BC surgery, and on the content of existing instruction forms. Appropriate versions were prepared for patients with high and low risk for side effects after surgery. The first drafts were validated by four experienced physical therapists certified in lymphedema treatments (PTCLTs). Then, pictures illustrating the exercises were added. The instruction forms were posted on physical therapy, BC, and lymphedema organization websites. Results: Information content includes the right of every patient to receive instruction after BC surgery followed by three sections: 1. exercise and early risk reduction for the first two days post-surgery; 2. instruction on exercise progression for the third day until the drains are removed, and the surgical scar has healed; 3. lifelong risk reduction recommendations. Conclusion: The development of standardized instruction forms up-dated to current evidence for patients after BC surgery answers a need expressed by patients and by physical therapists working in the field. The coincidence of the Covid-19 pandemic emphasized its relevance.